(untitled) (Research, Society and Development, 2021)
This paper analyzes the co-authorship network generated from the number of publications and interactions between the authors of the Programa de Pós-Graduação Multi-institucional em Difusão do Conhecimento (PPGDC) to verify whether, from the entry of new professors and students, there was a increase in the number of academic productions and co-authorships in the period 2017-2019. An exploratory approach was used as a methodology, based on the Social Network Analysis (SNA) and the literature review that investigated studies on the concept of SNA of co-authorship and scientific production, using the search engines: Science Direct and Google Scholar. Data collection took place through the CAPES Sucupira Platform. The reports have been generated in “.xls” format, using Microsoft Excel software. Based on the analyzes, the PPGDC intellectual production and co-authorship network was built and organized by the Pajek and Gephi tools. As the main result it was possible to observe that, due to the introduction of new participants to the Program, there was an increase in the number of authors and relationships between them. Despite this, it is noted that the network was made up of large connected groups, which publish intensely among their peers, but with little connection between these groups, highlighting the need for greater cooperation and scientific collaboration.